Hospitalized Patients' Satisfaction with Nursing Care Quality: A neurological Wards Focused Assessment - Kawthar Ali Dadoosh; Sadeq AL-Fayyadh (Kufa Journal for Nursing Sciences)
Background: Hospitalized patients in neurological wards require specialized nursing care. Patients’ satisfaction with the quality of nursing care is an important indicator for measuring the quality of nurses’ work. Patients are considered an important source for assessing the overall quality of hospital services, as well as the quality of nursing care in particular.